The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1516-14392006000300013
|View full text |Cite
|
Sign up to set email alerts
|

Compression tests of castor oil biopolymer

Abstract: Many methods have been developed to test and evaluate the mechanical properties of the biopolymer from castor oil employed in implants and osteo-repositions, among other things. Most of the methods are performed under quasi-static and cyclic loads (creep and relaxation tests) and under high strain rate, uniaxial compression conditions. This paper presents and discusses the development and applicability of a simple load-application apparatus, devised to reduce shear and barrelling effects on specimens and allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
1
3
0
2
Order By: Relevance
“…They showed that when the PDL is subjected to a continuous loading, it shows an elastic behavior followed by a viscoelastic phase. Figure 16 shows the viscoelastic behavior of the PDL which is in good agreement with the investigation of Ferneda et al [84] who studied the behavior of a viscoelastic material. They revealed the stress behavior of a viscoelastic material with loading, unloading, and reloading cycles.…”
Section: Discussionsupporting
confidence: 87%
“…They showed that when the PDL is subjected to a continuous loading, it shows an elastic behavior followed by a viscoelastic phase. Figure 16 shows the viscoelastic behavior of the PDL which is in good agreement with the investigation of Ferneda et al [84] who studied the behavior of a viscoelastic material. They revealed the stress behavior of a viscoelastic material with loading, unloading, and reloading cycles.…”
Section: Discussionsupporting
confidence: 87%
“…It is highlighted that in Fig. 9 the radial and the circumferential stresses vs time plots, shown the viscoplastic response generally displayed by polymers in compression [29,45,47], with the typical behavior of a softening after yield, followed by a plateau response, and an exponential increment of the stress for the low increment of strain.…”
Section: Viscoplastic Model Phenomenological Featuresmentioning
confidence: 89%
“…Figure 2 shows the representative Stress-strain experimental test curves. It is worth noting that until 20% strain no barreling effect was observed for the different strain rates used, i.e., the specimen deformed without displaying shearing and barreling [45].…”
Section: Compression Testmentioning
confidence: 94%
“…Entre as suas indicações clínicas incluem-se a fixação de próteses, a reconstituição e o preenchimento de espaços ósseos (Bioosteo, 2006), sendo em algumas situações uma alternativa ao polimetilmetacrilato. Ressalta-se que a maioria das publicações referentes ao emprego do polímero de mamona está associada a estudos in vivo, que analisaram biocompatibilidade, capacidade de estimulação na neoformação óssea, osteointegração e toxicidade (Kfuri et al, 2001;Rezende et al, 2001;Ignácio et al, 2002;Ziliotto et al, 2003;Laranjeira et al, 2004;Bolson et al, 2005;Pereira-Júnior et al, 2007), mas há poucos relatos sobre suas propriedades mecânicas (Claro Neto, 1997;Kfuri et al, 2001;Silva et al, 2001;Ferneda et al, 2006). Dessa forma, o objetivo deste trabalho foi avaliar o comportamento mecânico do polímero de mamona, quanto à carga máxima e à tensão à compressão, ao módulo e à resistência ao dobramento, tendo por variáveis o tempo de produção e a presença de catalisador, e utilizando como padrão comparativo o polimetilmetacrilato.…”
Section: Introductionunclassified